A New Multi-disciplinary Rehabilitation Outcome Checklist for the Rehabilitation of Total Knee and Total Hip Replacement Patients - Nang-Man Raymond Wong; Wai-Ling Cheung; Chi-Keung Ng; Kai-Kit Wong; See-Wai Lau; Tim Hung (Journal of Orthopaedics, Trauma and Rehabilitation, 2013)
Use of clinical pathways in the rehabilitation of total knee and total hip replacement patients is on an increasing trend. However, in the literatures there was no universally agreed assessment and auditing method on the outcome of these clinical pathways. We created a new multi-disciplinary rehabilitation outcome checklist (MROC) to evaluate and audit the outcome of our patients after total joint replacement. MROC was applied in 96 total knee and 18 total hip replacement patients. The compliance rate of MROC was 100%. Most of the treatment goals of the clinical pathways were found to be fulfilled. The MROC provides an easy-to-use, free-of-charge, and tailor-made checklist for the evaluation and auditing purpose.